The Influence of HR Development, Standard Operational Procedures, Work Facilities and Motivation on Employee Performance - Miska Irani TARIGAN; Melviola SITUMORANG (PT Keberlanjutan Strategis Indonesia, 2024)
The purpose of this research is to find out how human resource development, standard operating procedures, work facilities, and motivation affect employee performance. The quantitative research approach was utilized, the research with population of employee of PT. Mutifa, Medan. The sample was taken 50 respondents chosen by saturation sampling. Data analysis with multiple linear regression with SPSS application. The t test results reveal that human resource development, standard operating procedures, work facilities, and motivation all have a positive and statistically significant effect on employee performance. The F test demonstrates that human resource development, standard operating procedures, work facilities, and job motivation all have a positive and significant effect on employee performance at the same time. Employee performance can be explained by human variables, according to the coefficient of determination of 0.627.